2011
DOI: 10.1002/app.35352
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of fire behavior of rigid polyurethane foams containing fly ash and intumescent flame retardant by using a cone calorimeter

Abstract: Cone calorimeter is one of the most useful bench-scale equipment which can simulate real-world fire conditions. Therefore, cone calorimeter tests have been the most important and widely used tests for research and development of fire behavior of polymeric materials. In this study, fire behavior of rigid polyurethane foams containing fly ash (up to 5 wt %) and intumescent flame retardant (up to 5 wt %) composed of ammonium polyphosphate/pentaerythritol was investigated by using a cone calorimeter. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
12

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 82 publications
4
101
0
12
Order By: Relevance
“…FA can be added directly to polyurethane foams to increase its fire resistance. Usta (2012) showed that FA significantly enhanced fire resistance and thermal stability of polyurethane foams due to the inert nature of FA with fire. A similar effect was found with polycarbonate (Soyama et al 2007).…”
Section: Polymer Composite Materialsmentioning
confidence: 98%
“…FA can be added directly to polyurethane foams to increase its fire resistance. Usta (2012) showed that FA significantly enhanced fire resistance and thermal stability of polyurethane foams due to the inert nature of FA with fire. A similar effect was found with polycarbonate (Soyama et al 2007).…”
Section: Polymer Composite Materialsmentioning
confidence: 98%
“…boyunca 100 °C'de tutularak nem uzaklaştırılmıştır. APP/PER oranı 2/1 olarak uygulanmıştır [6], [28]. Rijit poliüretan köpük üretiminde izosiyanat/poliol oranı tedarikçi firmadan alınan tavsiye doğrultusunda 1.18/1 oranında ayarlanmıştır.…”
Section: Numunelerin Hazırlanmasıunclassified
“…NO emisyonunun düşük konsantrasyonlarda (~ 20 ppm) bile ciddi zararlara sebep olmasından dolayı yanma işlemlerinde mutlaka incelemeye alınması gerekli bir emisyon olarak değerlendirilmektedir [6], [37], [39], [40]. Poliüretan köpük malzemelerin içerisinde yer alan azot nedeniyle yanma veya bozunma esnasında HCN oluşabilmektedir [37].…”
Section: Pur+05kagunclassified
“…"11.15" Shanghai jiaozhou road big fire [1] and On February 9, 2009, CCTV fire events [2] .All this fire incidents of external wall insulation finally put forward higher requirements [3][4][5].Polystyrene (PS) thermal insulation material is widely used as external wall insulation materials [6]. Burning PS will generate black smoke and molten drops and is toxic [7][8], which will cause great harms to life.…”
Section: Introductionmentioning
confidence: 99%